Design and Validation of a Full Body Control Semi-Active Suspension Strategy for a Supercar. Issue 5 (2019) - Corno, Matteo; Galluppi, Olga; Panzani, Giulio; Sinigaglia, Andrea; Capuano, Paolo; Cecconi, Jacopo; Savaresi, Sergio M.
Abstract: The paper designs a semi-active suspension control strategy for a supercar. The control strategy aims at providing sprung mass stability in terms of heave, pitch and roll dynamics. Supercars dynamics are very demanding in that the vehicle has to provide excellent stability during pilot-induced sprung mass movements (braking, acceleration and turning) and a reasonable road disturbance isolation. The proposed control system is based on four independent modified sky-hook controllers and a centralized high-level controller that schedules the parameter of the sky-hook algorithms taking into account the driver's input. The paper implements the proposed algorithm on an instrumented supercar and validates the approach on a number of maneuvers.